Challenging boundaries: is cross-protection evaluation necessary for African swine fever vaccine development? A case of oral vaccination in wild boar - Cadenas-Fernández, Estefanía; Barroso-Arévalo, Sandra; Kosowska, Aleksandra; Díaz-Frutos, Marta; Gallardo, Carmina; Rodríguez-Bertos, Antonio; Bosch, Jaime; Sánchez-Vizcaíno, Jose M.; Barasona, Jose A. (Frontiers in Immunology, 2024)
African swine fever (ASF) poses a significant threat to domestic pigs and wild boar (Sus scrofa) populations, with the current epidemiological situation more critical than ever. The disease has spread across five continents, causing devastating losses in the swine industry. Although extensive research efforts are ongoing to develop an effective and safe vaccine, this goal remains difficult to achieve. Among the potential vaccine candidates, live attenuated viruses (LAVs) have emerged as the most promising option due to their ability to provide strong protection against experimental challenges. However, ASF virus (ASFV) is highly diverse, with genetic and phenotypic variations across different isolates, which differ in virulence. This study highlights the limitations of a natural LAV strain (Lv17/WB/Rie1), which showed partial efficacy against a highly virulent and partially heterologous isolate (Arm07; genotype II). However, the LAV's effectiveness was incomplete when tested against a more phylogenetically distant virus (Ken06.Bus; genotype IX). These findings raise concerns about the feasibility of developing a universal vaccine for ASFV in the near future, emphasizing the urgent need to assess the protective scope of LAV candidates across different ASFV isolates to better define their limitations.